The Concept of Ma’rifatun Nafs and Self Knowledge: Comparative Study of the Thoughts of Al Ghazali and Sigmund Freud - Muhammad Nafi; Fitri Tiara Mulyani; Fitria Nur Afifah (JOUSIP: Journal of Sufism and Psychotherapy, 2022)
Self-knowledge is a successful understanding of important things about oneself which helps in efforts to build a good and positive attitude towards oneself, to accept and develop oneself. The main attention is directed to the introduction of personality, recognition of self-potential and being able to map oneself regarding one's own strengths and weaknesses. The understanding of self-knowledge can be found in many perspectives, this time it will be discussed according to Al Ghazali's view from an Islamic point of view, and from a psychological perspective, namely Sigmund Freud, both of whom have something in common with their thoughts. The purpose of this research is to know the concept of ma'rifatun nafs and self-knowledge according to Al-Ghazali and Sigmund Freud, both of whom are figures of psychology from Eastern and Western cultures who have different characteristics. This type of research is library research with primary and secondary data collection methods and documentation. Data analysis used qualitative analysis. The results of the study stated that ma'rifatun nafs according to Al Ghazali includes three human characteristics, namely shifatul baha'im, shifatusy syayathin, and shifatul malaikah. Meanwhile, according to Sigmund Freud, self-knowledge by understanding one's psychological processes includes the conscious, preconscious, and unconscious levels. Ways to know yourself include self-introspection, knowing your outer self, knowing your inner self, always remembering the purpose of creation, monitoring yourself and asking for the opinions of others.